Parental Phubbing and Adolescents’ Cyberbullying Perpetration: A Moderated Mediation Model of Moral Disengagement and Online Disinhibition - Wang, Xingchao (Journal of interpersonal violence, 2022)
The current study sought to examine whether parental phubbing was significantly related to adolescents? cyberbullying perpetration and if moral disengagement mediated this relationship. We further examined whether online disinhibition moderated the direct and indirect relationships between parental phubbing and adolescents? cyberbullying perpetration. The participants included 2,407 adolescents from seven middle schools in China who completed the questionnaires regarding their experience with parental phubbing, moral disengagement, cyberbullying perpetration, and online disinhibition. Results indicated that adolescents with a high level of parental phubbing were likely to cyberbully others. Moral disengagement significantly mediated the relationship between parental phubbing and adolescents? cyberbullying perpetration. Furthermore, online disinhibition moderated the indirect relationship between parental phubbing and adolescents? cyberbullying perpetration. Specifically, the paths from parental phubbing to moral disengagement and from moral disengagement to cyberbullying perpetration became strengthened when adolescents experienced high levels of online disinhibition.